1998
DOI: 10.1046/j.1460-9568.1998.00336.x
|View full text |Cite
|
Sign up to set email alerts
|

The murine Y1 receptor 5′ upstream sequence directs cell‐specific and developmentally regulated LacZ expression in transgenic mice CNS

Abstract: The Y1 receptor for neuropeptide Y (NPY) is highly expressed in mammalian CNS where it mediates the activation of several neurobiological functions. We have previously demonstrated that a 1.3-kb fragment upstream of the transcription initiation sites of the murine Y1 receptor gene is able to direct specific expression of reporter genes in neuronal cell cultures. In the present study transgenic mice harbouring this putative promoter region linked to the LacZ reporter gene were generated and analysed for tempora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 48 publications
0
33
0
Order By: Relevance
“…We have recently generated transgenic mouse lines carrying the Y 1 receptor gene promoter/ LacZ fusion gene and we demonstrated that this transgenic model can be used to quantify changes in Y1 receptor gene expression in specific brain regions, induced, for instance, by pharmacological treatments [26, 44]. The analysis of the effect of estradiol on Y 1 receptor gene expression in the different hypothalamic nuclei from Y 1 R/Lac Z transgenic mice should then provide important information on the mechanisms involved in the steroid regulation of the NPY-mediated transmission.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently generated transgenic mouse lines carrying the Y 1 receptor gene promoter/ LacZ fusion gene and we demonstrated that this transgenic model can be used to quantify changes in Y1 receptor gene expression in specific brain regions, induced, for instance, by pharmacological treatments [26, 44]. The analysis of the effect of estradiol on Y 1 receptor gene expression in the different hypothalamic nuclei from Y 1 R/Lac Z transgenic mice should then provide important information on the mechanisms involved in the steroid regulation of the NPY-mediated transmission.…”
Section: Discussionmentioning
confidence: 99%
“…This DNA contains sufficient information to replicate the expression pattern of the endogenous Y 1 receptor gene in a CNS-restricted and developmental stage-specific manner in transgenic mice [25, 26]. Sequence analysis of this region revealed the presence of several potential responsive elements for known transcription factors, including three hemipalindromic estrogen-responsive elements (ERE) [27].…”
Section: Introductionmentioning
confidence: 99%
“…Adult female Y 1 R/LacZ mice from transgenic line 62 (body mass, 25–30 g) obtained from our breeding colony were used for the experiments (Oberto et al . 1998).…”
Section: Animalsmentioning
confidence: 99%
“…Expression of lacZ was analyzed by histochemical staining of coronal brain sections for β‐galactosidase activity, as previously described (Oberto et al . 1998).…”
Section: β‐Galactosidase Stainingmentioning
confidence: 99%
“…2000). We previously generated 10 independent transgenic mouse lines harbouring a fusion construct ( Y 1 R/LacZ ) that comprises the mouse Y 1 receptor gene promoter linked to the lacZ gene and whose expression pattern mimics that of the endogenous Y 1 receptor gene in a CNS‐restricted and developmental stage‐specific manner (Oberto et al . 1998).…”
mentioning
confidence: 99%